Sequential Non-overlapping Random Packing of Disks in a Square Box - Montenegro Joo, Javier (2008)
The total area occupied by equal disks randomly placed in a square region, one after another and without overlapping is investigated by means of Monte Carlo simulation, having as a reference the orderly placement of disks in the same region. It is found that the occupied area ranges from 56% to 65% of the area occupied if the disks were orderly placed.